(untitled) (Fiep Bulletin - online, 2014)
Using document analysis (DA), the study focused on the investigation of a Sports Project (EP) submitted to the Ministry of Sport, the body responsible for evaluating projects seeking financial support through the Federal Law for the Encouragement of Sports (LIE). Initially it was made ??a rescue of sports law and federal tax incentive mechanisms for amateur sport. Then we tried to portray the construction of the phenomenon, the concept of Sport, the dictates of the LIE and the current understanding of the federal government that concept forward. Concerning the analysis of the Draft Sports undergoing LIE, its central features were identified and compared to the requirements established by the Ministry of Sports for the reason LIE. We can learn that the process by which they must submit the PE that seek funding for LIE is too hard. It was noted that the difficulties begin in the joint document, permeates the preparation of PE, approval and raising funds. Directing the gaze to the preparation of PE were focused features like organization and clarity, technical and operational capacity of the applicant and the relevance of the theme, once again being able to identify obstacles to "hurt", excessively, players / tenderers who do not have professional assistance for development of PE